Impact of 10-minute interval roller massage on performance and active range of motion - Hodgson, D. D.; Quigley, P. J.; Whitten, J. H. D.; Reid, J. C.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2019)
Roller massage (RM) has been shown to increase range of motion (ROM) without subsequent performance deficits. However, prolonged static stretching (SS) can induce performance impairments. The objective of this study was to examine the effects of combining SS and RM with and without subsequent RM on ROM and neuromuscular performance. Subjects (n = 12) participated in 5 sessions: (a) SS only (SS_rest), (b) SS + RM (SS + RM_rest), (c) SS with RM at 10 and 20 minutes after stretch (SS_RM), (d) SS + RM with RM at 10 and 20 minutes after stretch (SS + RM_RM), and (e) control. For the SS conditions, the quadriceps and hamstrings received passive SS for 2 × 30 seconds each. For the SS + RM conditions, SS was applied to the quadriceps and hamstrings for 30 seconds each, and RM was performed for 30 seconds per muscle. SS_RM and SS + RM_RM conditions received an additional 30-second RM at 10 and 20 minutes after warm-up, whereas sessions without additional RM rested for the same duration. Testing measures included hip flexion (HF) and knee flexion (KF) active and passive ROM, hurdle jump height and contact time, countermovement jump height, and maximal voluntary isometric contraction force. Initial KF and HF ROM improvements provided by SS_RM and SS + RM_RM were sustained up to 30 minutes after intervention. Furthermore, SS_RM exhibited greater ROM compared with sessions lacking additional RM in active and passive HF as well as active and passive KF. Similarly, SS + RM_RM elicited greater KF and HF ROM improvements than SS_rest. In conclusion, active KF and HF ROM improvements were prolonged by additional RM, whereas neuromuscular performance remained relatively unaffected.